Firm wage premia, industrial relations, and rent sharing in Germany - Boris Hirsch; Steffen Mueller (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2018)
This paper investigates the influence of industrial relations on firm wage premia in Germany. OLS regressions for the firm effects from a two-way fixed effects decomposition of workers' wages by Card, Heining, and Kline (2013) document that average premia are larger in firms bound by collective agreements and in firms with a works council, holding constant firm performance. RIF regressions show that premia are less dispersed among covered firms but more dispersed among firms with a works council. Hence, deunionization is the only among the suspects investigated that contributes to explaining the marked rise in the premia dispersion over time.
Keywords: J31; J52; J53; 330; firm wage premium; industrial relations; trade unions; works councils; bargaining power; rent sharing; wage inequality; Germany